A Phase II Study of Ifosfamide, Methotrexate, Etoposide, and Prednisolone for Previously Untreated Stage I/II Extranodal Natural Killer/T‐Cell Lymphoma, Nasal Type: A Multicenter Trial of the Korean Cancer Study Group. (3rd October 2014) - Kim, Tae Min; Kim, Dong‐Wan; Kang, Yoon‐Koo; Chung, Jooseop; Song, Hong‐Suk; Kim, Hyo Jung; Kim, Byung Soo; Lee, Jong‐Seok; Kim, Hawk; Yang, Sung Hyun; Yuh, Young Jin; Bae, Sung Hwa; et al.
Abstract : Background: Combination chemotherapy consisting of ifosfamide, methotrexate, etoposide, and prednisolone (IMEP) was active as first‐line and second‐line treatment for extranodal natural killer/T‐cell lymphoma (NTCL). Methods: Forty‐four patients with chemo‐naïve stage I/II NTCL were enrolled in a prospective, multicenter, phase II study and received six cycles of IMEP (ifosfamide 1.5 g/m 2 on days 1–3; methotrextate 30 mg/m 2 on days 3 and 10; etoposide 100 mg/m 2 on days 1–3; and prednisolone 60 mg/m 2 per day on days 1–5) followed by involved field radiotherapy (IFRT). Results: Overall response rates were 73% (complete remission [CR] in 11 of 41 evaluable patients [27%]) after IMEP chemotherapy and 78% (CR 18 of 27 evaluable patients [67%]) after IMEP followed by IFRT. Neutropenia and thrombocytopenia were documented in 33 patients (75%) and 7 patients (16%), respectively. Only 8 patients (18%) experienced febrile neutropenia. Three‐year progression‐free survival (PFS) and overall survival (OS) were 66% and 56%, respectively. High Ki‐67 (≥70%) and Ann Arbor stage II independently reduced PFS ( p = .004) and OS ( p = .001), respectively. Conclusion: Due to the high rate of progression during IMEP chemotherapy, IFRT needs to be introduced earlier. Moreover, active chemotherapy including an l ‐asparaginase‐based regimen should be use to reduce systemic treatment failure in stage I/II NTCL. Abstract : 摘要 背景 . 异环磷酰胺、甲氨蝶呤、依托泊苷以及泼尼松龙（IMEP）联合化疗是结外鼻型自然杀伤/T 细胞淋巴瘤（NTCL）的有效一线和二线治疗。 方法 . 本次前瞻性、多中心、 II 期研究入组 44 例既往未接受过化疗的 I/II 期 NTCL 患者，给予 IMEP 6 周期治疗（异环磷酰胺 1.5 mg/m 2 ，第 1∼3 天；甲氨蝶呤 30 mg/m 2 ，第 3、10 天；依托泊苷 100 mg/m 2 ，第 1∼3 天；泼尼松龙 60 mg/m 2 ，第 1∼5 天），继以受累野放疗（IFRT）。 结果 . IMEP 化疗后，总缓解率为 73%[11/41 例可评估患者完全缓解（CR，27%）]，IMEP 继以 IFRT 后，总缓解率为 78%[18/27 例可评估患者 CR（67%）]。确认的中性粒细胞减少和血小板减少分别为 33 例（75%）和 7 例（16%）。仅 8 例患者（18%）发生发热性中性粒细胞减少。3 年无进展生存（PFS）率和总生存（OS）率分别为 66% 和 56%。高Ki‐67（≥ 70%）和 Ann Arbor II 期与 PFS（ p =0.004）和 OS（ p =0.001）较短独立相关。 结论 . 由于 IMEP 化疗期间疾病进展率很高，IFRT 需要早期给予。而且，应该使用包括基于左旋门冬酰胺酶的方案在内的有效化疗，以减少 I/II 期 NTCL 的系统性治疗失败。 The Oncologist 2014;19: 1129‐1130